Pandangan Carl Gustav Jung Terhadap Psikologi Kepribadian - Risydah Fadilah; Febri Adhari; Ichsani Walidaini (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to find out about the theory of personality put forward by Carl Gustav Jung. Individual personality according to Jung can be viewed prospectively and retrospectively. The prospective view is to look at the personality to the individual's development in the future. Retrospective view is concerned with the past of the person. Jung's analysis theory states that the individual's personality is divided into three levels of consciousness, namely consciousness and ego, personal and complex unconscious, and collective unconscious and archetypes. This journal uses a qualitative research method which is by conducting case studies: this case study method involves in-depth research about individuals or small groups using a qualitative approach. In case studies, the researcher studies the life experiences and stories of individuals or groups to identify underlying psychological patterns, archetypes, and conflicts. Debates about the meaning of humans are very diverse and seem to have never stagnated in line with the development of human civilization which continues to change. Carl Gustav Jung, who is a psychoanalytic figure, related his thoughts on the collective unconscious and later on the organismal philosophy of Alfred North Whitehead who tried to reveal the natural characteristics of human beings. This study seeks to compare the thoughts of Carl Gustav Jung to achieve a deep understanding of the basic concepts of the human self.